Students' Mathematical Investigation: A Review Based on Disposition and Self-Esteem - Komala, Elsa; Salsiah, Usi; Sugiarni, Rani (PRISMA, 2025)
Students’ mathematical investigation ability is influenced not only by cognitive knowledge but also by affective factors such as mathematical disposition and self-esteem. This study aims to examine the relationship between mathematical disposition and students’ mathematical investigation ability, investigate the predictive influence of self-esteem on investigation ability, and analyze the combined contribution of both variables. This quantitative study involved 49 eleventh-grade students from a private high school in Cianjur Regency in the 2024/2025 academic year, with class XI-1 selected through purposive sampling. Research instruments included mathematical disposition and self-esteem questionnaires, as well as a mathematical investigation test on circle material. Interviews with several students were conducted to support the test findings. Data were analyzed using simple and multiple linear regression after verifying classical assumptions. The results showed that mathematical disposition had a significant relationship with mathematical investigation ability (40.2%), while self-esteem demonstrated a non-significant predictive influence (18.7%). Together, mathematical disposition and self-esteem contributed 31.6% to students’ mathematical investigation ability. These findings highlight the importance of fostering mathematical disposition as a potential predictor of students’ investigation ability.